(untitled) (Andamios, Revista de Investigación Social, 2012)
This text is to show how articulate the political and epistemological perspective in the work of Bolivian sociologist René Zavaleta. The central concept to develop its complex work will be to all. Rene Zavaleta has been perhaps the most important theoretical Bolivia during the twentieth century and his work is still of great importance to today.